Rapid enzymatic-gravimetric determination of dietary fiber content of dessicated coconut - Reyes, Arturo Lacaba; De Leon, Sonia Y. (1993.)
The physical properties and dietary fiber content of dessicated coconut was evaluated and determined in view of it being a potential source of dietary fiber. The sample was obtained from a commercial manufacturing plant of dessicated coconut after paring, drying, and disintegrating. The deoiled, sugar-free sample of DCN showed a crude fiber content of 41.52%; moisture content of 3.15%; crude fat content of 42.46%; crude protein content of 5.23%; and an ash content of 2.52%. Three different techniques of density determination were employed that yielded the following results: direct density-0.258 g/ml, bulk density-0.280 g/mL, and water displacement-0.50 g/ml, Water-holding capacity was 4.680 mL/g and pH was found to be 6.96. Soluble dietary fiber was found to be 53.93% in the dessicated coconut. Total dietary fiber was 78.45% of the sample and insoluble dietary fiber, 24.66%. Enzymatic-Gravimetric determination of the sample was carried out using the AOAC-AACC accepted procedure for determining insoluble dietary fiber.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut